(untitled) (Homoeopathy for All, 2025)
Background: Hypothyroidism is a common endocrine disease in the world, which is characterized by decreased thyroid hormone formation and secretion, leading to extreme fatigue, weight gain, cold intolerance, depression, loss of appetite, dryness, hair fall, female problems like menstrual cycle, infertility, and various metabolic problems. Modern medical treatment with levothyroxine with side effects. Homeopathic System, a holistic and individualized system of homeopathic medicine, has a significant effect in managing hypothyroidism. Aim and Objective: This Comprehensive Review aims to evaluate and synthesize clinical evidence on the effectiveness of homeopathic medicine in the management of hypothyroidism and subclinical hypothyroidism. The objective is to assess the significant impact of individualized and constitutional homeopathic medicine on thyroid function, primarily improving TSH levels and associated signs and symptoms. Methodology: A Comprehensive literature review search was conducted using online databases such as PubMed, Scopus, and Google Scholar for articles published between January 2020 and December 2024. Keywords included "hypothyroidism," "homeopathic treatment," "homeopathy," and "homeopathic management." Out of 50 retrieved articles, six met the inclusion criteria. Results:Out of 50 retrieved articles, six met the inclusion criteria in the Comprehensive Review. The Comprehensive Review of studies consistently demonstrated significant improvements in TSH value, Zulewski’s clinical scores, and patient-reported outcomes after homeopathic treatment. Conclusion: The findings of this Comprehensive Review suggest that individual homeopathic medicines may have promising benefits in the management of signs and symptoms of hypothyroidism.